Influence of the Tourniquet on Pain and Function in Total Knee Arthroplasty: a Systematic Review and Meta-Analysis - Jawhar, Ahmed; Skeirek, Dania; Stetzelberger, Vera; Obertacke, Udo (Zeitschrift für Orthopädie und Unfallchirurgie, 2019)
Background The use of the tourniquet in total knee arthroplasty is still a subject of controversial discussion. Previous studies mainly focus on parameters like blood loss and operation time. The aim of this systematic review is to evaluate the postoperative outcome involving parameters such as pain intensity, analgesic consumption, knee function and complication rate with and without tourniquet use, to find a recommendation for future application in total knee arthroplasty.Material and Methods This review is based on the PRISMA Checklists. A systematic research was performed in PubMed using the key words “tourniquet”, “total knee arthroplasty”, “TKA” and “knee endoprosthesis” up to and including January 2018. The initial search revealed 686 Papers which were extracted by the parameters intensity of pain, analgesic consumption, function (range of motion, Hospital for Special Surgery Score, Knee Society Score) and complications (deep vein thrombosis, surgical side infection, pulmonary embolism). The program Review Manager Version 5.3 was used for statistical analysis. A significance level of p < 0,05 was defined.Results 18 studies were included in this review with 1279 total knee arthroplasties overall (646 with the use of tourniquet and 633 without). The analysis shows a significant lower pain intensity until the fifth postoperative day (p = 0,03) and also after one to three months (p = 0,04) without using the tourniquet. Range of motion is significantly higher in two to three days postoperatively (p < 0,00 001) when the surgery was performed without tourniquet. Knee Society Score shows no difference between the two groups. A deep vein thrombosis appears significantly more often when using a tourniquet (p = 0,04). There was no higher occurrence in pulmonary embolism and surgical side infections.Conclusion The use of a pneumatic tourniquet in total knee arthroplasty affects especially the early postoperative pain and functional recovery.
Keywords: tourniquet; total knee arthroplasty; pain; function; complication